2019
DOI: 10.3311/ppch.14051
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analyses of Proteins Coordinating G2 Size Control in Fission Yeast

Abstract: Regulation of G2 phase is based on inhibition of MPF (M-phase Promoting Factor) through phosphorylation by Wee1-like kinases. Removal of the inhibiting phosphate group requires Cdc25-like phosphatases. In fission yeast, size control is achieved by monitoring cell length via interactions of Pom1, Nif1, Cdr1 and Cdr2 proteins, regulating MPF via the Wee1 kinase. Here, a search for homologues of these key proteins was performed in the genomes of several model organisms to analyze the evolution of G2 size control.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…3 a). Duplication of WEE1 genes is not restricted to legumes and plants but has already been documented in metazoans and fungi 20 . Using only two plant sequences, Sorrel et al 4 found that the catalytic domain was conserved across animals and plants and that the two plants sequences grouped together.…”
Section: Introductionmentioning
confidence: 98%
“…3 a). Duplication of WEE1 genes is not restricted to legumes and plants but has already been documented in metazoans and fungi 20 . Using only two plant sequences, Sorrel et al 4 found that the catalytic domain was conserved across animals and plants and that the two plants sequences grouped together.…”
Section: Introductionmentioning
confidence: 98%
“…As a consequence, mitotic onset might happen only if the cell has reached a critical length. It is also noteworthy that some of these upstream regulators (like Wee1 and Cdc25) of Cdk in G2 phase are evolutionarily conserved, whereas others (like Pom1 and Cdr2) are present only in fission yeasts (Nagy, Medgyes‐Horváth, Szalay, Sipiczki, & Sveiczer, 2019; Sorrell et al, 2002). This may probably be a consequence of the special geometry (cylindrical form with constant diameter) of these yeast cells, which is common in prokaryotes, but very rare in eukaryotes.…”
Section: Introductionmentioning
confidence: 99%
“…Analysing the wee1-50 mutant is interesting, as cells of this mutant are small and have a generation time similar to WT, but have quite different distribution of cell cycle phases compared to WT [44,45]. The protein encoded by the wee1 gene is a highly conserved cell cycle regulator among eukaryotes [46,47]. The pom1 gene encodes an upstream regulator of the Wee1 protein, which is localized in the cell cortex with a decreasing spatial gradient from the poles to the middle of the cell [14,48].…”
Section: Growth Patterns In Different Cell Culturesmentioning
confidence: 99%
“…Moreover, a large number of cells are worth being involved in the analyses. It is noteworthy that the Pom1 protein is not conserved at all, but is unique to the genus Schizosaccharomyces [47].…”
Section: Growth Patterns In Different Cell Culturesmentioning
confidence: 99%